PENERAPAN MODEL PEMBELAJARAN METAKOGNITIF UNTUK MENINGKATKAN MOTIVASI BELAJAR DI MAN 1 KOTA MAKASSAR - Nurmida; Raehana, Syarifa; Wahab, Abdul; Mustamin; Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' learning motivation through the application of metacognitive learning models in the subject of Akidah Akhlak in class X.6 MAN 1 Makassar City. This study is motivated by the low learning motivation of students indicated by the lack of activeness, enthusiasm, and involvement in the learning process. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model which is implemented in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. The research subjects were 32 students of class X.6 MAN 1 Makassar City. Data collection techniques include observation, interviews, questionnaires, and documentation. Data were analyzed qualitatively and quantitatively using average and percentage calculations. The results of the study show that the application of metacognitive learning models is able to improve students' learning motivation in each cycle. In the pre-cycle stage, the average learning motivation of students was 72.62% with a good category. After the implementation of the action in cycle I, learning motivation increased to 77.28%, but has not yet reached the success indicator set at 80%. Learning improvements were then carried out in cycle II by optimizing the metacognitive stages, namely planning, monitoring, and evaluating, so that the average learning motivation increased to 88.50% with a very good category. The results of observations also showed an increase in student learning activities, such as the courage to express opinions, ask questions, discuss, collaborate, and the ability to plan, monitor, and evaluate the learning process. Thus, it can be concluded that the application of the metacognitive learning model is effective in increasing student learning motivation in the subject of Akidah Akhlak in class X.6 MAN 1 Makassar City.